Қазақша ойлау мен қазақша сөйлеудің практикалық дағдыларын қалыптастыру аясында дарынды балалардың танымдық сұраныстарын қанағаттандыру - Қозғанбаева, М.Т. (My University, 2013)
This article deals with the satisfaction of cognitive needs of gifted children, the initiation of cognitive activity of gifted children through the organization of in-depth teaching of the official language, student-centered components.